If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -6) + -1(y + 2) = 26 Reorder the terms: 2(-6 + y) + -1(y + 2) = 26 (-6 * 2 + y * 2) + -1(y + 2) = 26 (-12 + 2y) + -1(y + 2) = 26 Reorder the terms: -12 + 2y + -1(2 + y) = 26 -12 + 2y + (2 * -1 + y * -1) = 26 -12 + 2y + (-2 + -1y) = 26 Reorder the terms: -12 + -2 + 2y + -1y = 26 Combine like terms: -12 + -2 = -14 -14 + 2y + -1y = 26 Combine like terms: 2y + -1y = 1y -14 + 1y = 26 Solving -14 + 1y = 26 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 1y = 26 + 14 Combine like terms: -14 + 14 = 0 0 + 1y = 26 + 14 1y = 26 + 14 Combine like terms: 26 + 14 = 40 1y = 40 Divide each side by '1'. y = 40 Simplifying y = 40
| (x^2+16)(x^3-108)=0 | | 14a+12=84 | | 9[(4+4)-2]= | | .1(x^2+16)(x^3-108)=0 | | 4=5-3x | | -5(t-4)-7= | | 17=-5x-13 | | 6x+1=4x-3 | | 14=18-4x | | 1/9(p+18)+1/3(2p+3)=p+3 | | 2=-x-5 | | 13q-13q=22 | | (a-3)(1+7)-2=14 | | 3x-12x^2+x-12=0 | | -9+-6= | | a-3=-15 | | 3-2x(x-1)=x(3-2x)-(x-3) | | -2(r+7)=-35 | | x^100+x^2+1=0 | | -1/4(x-12)+1/2(x+2)=x+4 | | 2(x-3)=9 | | 65-2x=43x+15 | | -5=3m-13 | | 12-2(y+5)=4(y-7)-(y-1) | | y=5Inx | | 6.1=7.7-0.8x | | 12y=2x-6 | | 3m+3=2m+4 | | 2(5x-4)=11x | | graphy+9=5(x+6) | | 2x-9=8x+3 | | 1/7(3x+2)-1/5(x+4)=2 |